Peran Transaksi Pihak Berelasi dalam Penghindaran Pajak Perusahaan - Tifanny Suhendra Hardiansyah; Rini Indriani (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to examine the effect of related party transactions on tax avoidance in primary consumer goods companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Method: This study uses a quantitative approach with multiple linear regression analysis. The population consists of primary consumer goods companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The sampling technique used is purposive sampling, resulting in 87 firm-year observations. Tax avoidance is measured using Cash Effective Tax Rate (CETR), while related party transactions are proxied by related party receivables, related party payables, related party purchases, and related party sales. Control variables include firm size, profitability (ROA), and leverage (DER). Finding: The results show that related party sales and related party payables significantly affect tax avoidance, indicating that higher related party transactions increase the tendency of companies to engage in tax avoidance. Meanwhile, related party receivables and related party purchases do not significantly affect tax avoidance. This indicates that not all related party transactions are used as tax avoidance strategies, but only transactions that directly influence taxable income. Novelty: This study provides novelty by applying factor analysis to group four proxies of related party transactions into two new factors, namely RPT1 and RPT2, which simplify the regression model and provide a clearer understanding of which types of related party transactions are more closely associated with tax avoidance practices.